The mechanics of running while approaching and jumping over an obstacle - Mauroy, G.; Schepens, B.; Willems, P. A. (European Journal of Applied Physiology, 2013)
When leaping an obstacle, the runner increases the vertical velocity of his/her centre of mass (COM) at takeoff to augment the amplitude and duration of the aerial phase over it. This study analyses the modification of the bouncing mechanism of running when approaching a barrier. The forces exerted by the feet on the ground are measured by a 13-m-long force platform during the four to nine running steps preceding the jump over a 0.45- to 0.85-m-high barrier, at an approaching speed between 9 and 21 km/h. The movements of the COM are evaluated by time-integration of the forces and the stiffness of the bouncing system by computer simulation. The running mechanism is modified during the two steps preceding the barrier. During the contact period, two steps before the barrier, the leg-spring stiffness decreases; consequently, the COM is lowered and accelerated forward. Then during the contact period preceding the obstacle, the leg-spring stiffness increases and the COM is raised and accelerated upwards, whereas its forward velocity is reduced. During this phase, the leg-spring acts like a pole, which stores elastic energy and changes the direction of the velocity vector to release this energy in a vertical direction. At high speeds, this storage-release mechanism of elastic energy is sufficient to provide the energy necessary to leap the obstacle. On the contrary, at low speeds, the amount of elastic energy stored and released in the leg-spring is not sufficient to jump over the obstacle and additional positive muscular work must be done.